2022
DOI: 10.1093/stmcls/sxac025
|View full text |Cite
|
Sign up to set email alerts
|

FGF10 Triggers De Novo Alveologenesis in a Bronchopulmonary Dysplasia Model: Impact on Resident Mesenchymal Niche Cells

Abstract: Bronchopulmonary dysplasia (BPD) is a neonatal lung disease developing in premature babies characterized by arrested alveologenesis and associated with decreased Fibroblast growth factor 10 (FGF10) expression. One-week hyperoxia (HYX) exposure of newborn mice leads to a permanent arrest in alveologenesis. To test the role of Fgf10 signaling to promote de novo alveologenesis following hyperoxia, we used transgenic mice allowing inducible expression of Fgf10 and recombinant FGF10 (rFGF10) protein delivered intra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 44 publications
(56 reference statements)
0
10
0
Order By: Relevance
“…This may represent an additional feature of the BPD ( Chao et al, 2019 ). However, a recent study showed that overexpression of Fgf10 and administration of rFGF10 rescued alveologenesis defects in transgenic mice ( Taghizadeh et al, 2022 ).…”
Section: Survey Methodologymentioning
confidence: 99%
“…This may represent an additional feature of the BPD ( Chao et al, 2019 ). However, a recent study showed that overexpression of Fgf10 and administration of rFGF10 rescued alveologenesis defects in transgenic mice ( Taghizadeh et al, 2022 ).…”
Section: Survey Methodologymentioning
confidence: 99%
“…FGF10 is synthesized by submesothelial cells and binds to fibroblast growth factor receptor 2b (FGFR2B), which was shown to be regulated by TLR2/4-NFKB signaling [ 121 ]. Reduced levels of FGF10 were repeatedly illustrated in tracheal aspirates and lung explants of BPD patients [ 47 , 114 ], while transgenic mice overexpressing FGF10 seem to preserve the normal lung structure [ 122 ]. In one latest pioneer preclinical study, i.p administration of recombinant FGF10 triggered de novo alveologenesis in newborn mice with pre-existing BPD-like injuries [ 122 ].…”
Section: Signaling Network Underlying Iai-driven Lung Injury and Pote...mentioning
confidence: 99%
“…Reduced levels of FGF10 were repeatedly illustrated in tracheal aspirates and lung explants of BPD patients [ 47 , 114 ], while transgenic mice overexpressing FGF10 seem to preserve the normal lung structure [ 122 ]. In one latest pioneer preclinical study, i.p administration of recombinant FGF10 triggered de novo alveologenesis in newborn mice with pre-existing BPD-like injuries [ 122 ]. Despite being a hyperoxia mouse model, it pointed towards the potential of FGF10 as a promising therapeutic approach to be further validated by preclinical IAI models, given that FGF10 is regulated by both infectious and hyperoxia insults [ 78 , 99 , 114 , 122 ].…”
Section: Signaling Network Underlying Iai-driven Lung Injury and Pote...mentioning
confidence: 99%
See 1 more Smart Citation
“…Hyperoxic injury is one of the main risk factors in BPD pathogenesis, which is thought to disrupt critical signaling pathways that induce lung development, including branching and septation [ 76 ]. Several signaling pathways contributing to these processes have been described, such as IGFR [ 5 ], FGF10 [ 77 , 78 ], and TGF-β [ 79 ] signaling pathways, where the IRS proteins might serve as a common component ( Figure 3 ) [ 80 , 81 ].…”
Section: Possible Roles Of Irs In Pediatric Lung Diseasesmentioning
confidence: 99%